Primary Squamous Cell Carcinoma of the Breast during Pregnancy: A Case Report - John Adi Ashindoitiang; Francis Adedayo Faduyile; Olufemi Joshua Taiwo (Case Reports in Medicine)
Primary squamous cell carcinoma of the breast (SCCB) is a very rare malignancy of the breast and is generally aggressive. It is even rarer during the gestational period. Only few cases have been reported during pregnancy and lactation (Rokutanda et al., 2000). SCCB seen within the gestational period tends to be very aggressive and has a larger size than other breast carcinomas. Pure SCCB is derived from the epidermis of the breast, nipple, or metaplasia on chronic inflammatory background (Bige et al., 2007), such as complicated breast cyst, dermoid cyst, or abscess. We report a case of SCCB in a 30-year-old primigravida that had an aggressive propensity and fatal outcome.